Optimization of Antiseptic Paper Soap through Varying NaOH Concentration: Combination of Cooking Oil, Citronella Oil, and Aloe Vera - Azwar, Azwar; Thaib, Anwar; Fajar, Chaidir; Priatna, Adjie August; Zanil, Mohd Fauzi (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractAntiseptic paper soap is convenient because it is flexible, safe for the skin, easily foams, and relatively affordable. Measuring the ratio between the concentrations of NaOH, cooking oil, citronella oil, and aloe vera additives is needed to improve the quality of antiseptic paper soap. Testing the saponification rate, density, pH, water content, fatty acid (FA) level, and free alkali content is critical to determine the characteristics of antiseptic paper soap so that it meets the standards for solid bath soap according to SNI 3532-2021 which is closest to the characteristics of paper soap because SNI for paper soap is not yet available. The weight ratio of citronella oil to cooking oil used is 1:1, 1:2, and 1:3. The NaOH concentrations used were 30%, 40%, and 50% w/v. The natural additives used are 0%, 5%, and up to 10% of the total mass. The research results showed that saponification value of the antiseptic paper soap produced was 197.724 milligrams KOH/gram up to 206.138 milligrams KOH/gram, the pH of the antiseptic paper soap was 9.1-10.6, the water content value was 10.940%-23.863%, the alkali content value free is 0.044%-0.104%, total fatty acid (FA) content is 29.688%-45.734%. The best antiseptic paper soap is produced using 30% w/v NaOH with a weight ratio of citronella oil to cooking oil used of 1:1 and natural additives (aloe vera) 5% of the total mass.Keywords: aloe vera, antiseptic, citronella oil, cooking oil, paper soap AbstrakSabun kertas antiseptik adalah sabun yang sangat praktis karena fleksibel, aman untuk kulit, mudah berbusa, dan harganya relatif terjangkau. Pengukuran rasio antara konsentrasi NaOH, minyak goreng, minyak serai wangi, dan aditif lidah buaya perlu dilakukan untuk meningkatkan kualitas sabun kertas antiseptik. Pengujian laju penyabunan, densitas, pH, kadar air, tingkat asam lemak (FA), dan kadar alkali bebas sangat penting untuk menentukan karakteristik sabun kertas antiseptik agar memenuhi standar sabun mandi padat sesuai SNI 3532-2021 yang paling mendekati karakteristik sabun kertas karena SNI untuk sabun kertas belum tersedia. Rasio berat minyak serai wangi terhadap minyak goreng yang digunakan adalah 1:1, 1:2, dan 1:3. Konsentrasi NaOH yang digunakan adalah 30%, 40%, dan 50% b/v. Bahan tambahan alami yang digunakan adalah 0%, 5%, hingga 10% dari massa total. Hasil penelitian menunjukkan bahwa bilangan penyabunan sabun kertas antiseptik yang dihasilkan adalah 197,724 miligram KOH/gram hingga 206,138 miligram KOH/gram, pH sabun kertas antiseptik adalah 9,1-10,6, nilai kadar air adalah 10,940%-23,863%, nilai kadar alkali bebas adalah 0,044%-0,104%, total kandungan asam lemak (FA) adalah 29,688%-45,734%. Sabun kertas antiseptik terbaik dihasilkan dengan menggunakan 30% b/v NaOH dengan rasio berat minyak serai wangi terhadap minyak goreng yang digunakan adalah 1:1 dan bahan tambahan alami (aloe vera) 5% dari total massa.Kata kunci: antiseptik, lidah buaya, minyak goreng, minyak serai wangi, sabun kertas